HEARING AND SPEECH IN CHILDREN WITH COCHLEAR IMPLANTS DEVELOPMENT (Academia Science Repository, 2023)
The author covers important problems of medical, psychological and pedagogical rehabilitation of children, which had undergone such surgery. The necessity of cooperation between doctors, psychologists, deaf-and-dumb pedagogues and the child’s family in order to achieve a successful restoration of the lost skills or to form new ones: perception of sound, speaking skills, social adoptation is being stressed.